2008
DOI: 10.2527/jas.2007-0372
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt supplied per os reduces the mammary Δ9-desaturase index of bovine milk1

Abstract: Results indicated that the dual marker system of Yb-acetate and Co-EDTA supplied per os reduced the proportion of fatty acids in bovine milk that were products of Delta (9)-desaturase. To verify this effect and identify the responsible marker component, 18 cows (3 cows per treatment) were administered per os a 0.25-L solution of either Co-acetate, Co-EDTA, Co-EDTA + Yb-acetate, EDTA, Yb-acetate, or water twice daily for 5 d. The daily amounts of Co, Yb, and EDTA were, respectively, 3.50, 3.44, and 21.00 g per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 29 publications
7
28
2
Order By: Relevance
“…This study confirmed the results of Shingfield et al. (2008) and Taugbøl et al. (2008), who found that a high amount of ruminal or per os supplemented Co reduced the Δ 9 ‐desaturase indices in bovine milk fat.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study confirmed the results of Shingfield et al. (2008) and Taugbøl et al. (2008), who found that a high amount of ruminal or per os supplemented Co reduced the Δ 9 ‐desaturase indices in bovine milk fat.…”
Section: Discussionsupporting
confidence: 91%
“…Within each Latin Square, treatment was administered on days 1–5, and days 6–14 were the depuration period. Treatment 1 consisted of per os supplementation of 0.25 l of a 9 g/l solution of Co‐acetate twice daily, corresponding to 3.5 g Co per day (Taugbøl et al., 2008). In Treatment 2, 450 mg Co‐acetate diluted in 250 ml 0.9% saline solution was injected into the jugular vein twice daily, at 8:00 and 15:30 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the high response of milk trans-9, trans-11-CLA in goats receiving sunfl ower oil could play a direct role in the typical decrease of milk FA desaturation ratios in this animal species (Table 13.2 ). Otherwise, abomasal infusions in cows and ewes (Griinari et al 2000 ;Corl et al 2001 ;Kay et al 2004 ;Bichi et al 2012 ) of sterculic oil, known as a strong inhibitor of SCD, and administration of Co-EDTA in the rumen or per os (Shingfi eld et al , 2008aTaugbøl et al 2008Taugbøl et al , 2010Karlengen et al 2012 ) decreased the milk FA desaturation ratios without alteration of mammary SCD1 mRNA abundance (Karlengen et al 2012 ) and without decreasing milk fat secretion. It was hypothesized (Shingfi eld et al 2008a ) that Cobalt interferes with the transfer of electrons from cytochrome b5 to the di-iron protein center of the terminal desaturase protein, thus altering the oxidation-reduction reactions of the conversion of the acyl-CoA substrates.…”
Section: In Vivo Studies With Specifi C Fatty Acid Infusion or Injectionmentioning
confidence: 99%